2005
DOI: 10.1021/jo0510033
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cross-Coupling in the Synthesis of Pyridinyl Boxazomycin C Analogues

Abstract: [reaction: see text] Palladium-catalyzed cross-coupling of 2-thiomethylbenzoxazoles with tri-alkylstannyl pyridines efficiently produces pyridinyl boxazomycin C analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Examples of ring systems include, bromooxabicyclo[3.2.1]octadiene [28], 5-trifloxyindoles [29], 6-halopurines [30] and 3,5-dichloro-2(H)-1,4-oxazin-2-one [31]. A palladium-catalyzed coupling of a 2-thiomethylbenzoxazole with a 2-pyridyltin reagent was used in a synthesis of pyridinyl boxazomycin C analogs [32].…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…Examples of ring systems include, bromooxabicyclo[3.2.1]octadiene [28], 5-trifloxyindoles [29], 6-halopurines [30] and 3,5-dichloro-2(H)-1,4-oxazin-2-one [31]. A palladium-catalyzed coupling of a 2-thiomethylbenzoxazole with a 2-pyridyltin reagent was used in a synthesis of pyridinyl boxazomycin C analogs [32].…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…In independent studies, our group has shown that the carboxylate counterion is not essential for the catalytic cycle to proceed with stannane derivatives, and can be efficiently replaced by the readily accessible copper(I) bromide−dimethyl sulfide complex (CuBr ·Me 2 S) . This approach has been recently successfully applied to various substrates …”
mentioning
confidence: 99%